Computer Hardware Maintenance Management Application Design at Socfin Indonesia Ltd. - Mulya Alfan (Journal of Computer Science and Informatics Engineering, 2022)
Socfin Indonesia is one of the companies engaged in the plantation sector and utilizes a computer system as a medium in carrying out its activities. The devices used in this system of course require maintenance and maintenance on a scheduled basis or under certain circumstances with the presentation of maintenance reports and computer hardware repairs that are still done manually and do not have a system or go through a computerized process. To improve the system, it is necessary to have a new computer-based design system to overcome these problems. The formulation of the problem in writing this journal is how to design a computer hardware maintenance management system at PT. Socfin Indonesia using Apache NetBeans IDE 12.5. This application will be built using the waterfall model software development method with the aim that in designing this application the work process can be carried out in well-structured stages. With this in mind, the author is interested in a computer hardware management application at PT. Socfin Indonesia, where this will increase the efficiency of working time utilization.